Efektivitas Pengelolaan Dana BOS Berbasis e-RKAS Pada SD GMIM Sion Tompaso Baru: - Meilani Marshanda Liow; Ramon A, F, Tumiwa; Miryam P, Lonto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
The management of School Operational Assistance (BOS) funds requires the principles of autonomy, participation, and accountability to improve the quality of education, with effectiveness measured by the alignment of budget implementation with technical guidelines. This descriptive qualitative study aims to analyze the effectiveness of BOS fund management based on the e-RKAS system at SD Gmim Sion and to identify obstacles to accountability. Data were collected through observation, documentation, and interviews with school officials, the committee, and parents, which were then analyzed using the Miles and Huberman interactive model and validated through triangulation. The results indicate that the management of BOS funds using the e-RKAS platform -RKAS platform at GMIM Sion Elementary School has been successful, with an 80% implementation rate, as evidenced by the fulfillment of key effectiveness criteria, including proper planning, compliance with BOS technical guidelines during implementation, transparency in financial reporting, and success in achieving the intended objectives of using the funds to support the school’s operational needs. In addition, the use of e-RKAS has led to improvements in administrative structure, transparency, and accountability in financial oversight through a digitally integrated approach to record-keeping and reporting. However, there are still several obstacles hindering the successful implementation of e-RKAS, such as a lack of skills among administrators in managing.